A decade of plague in Madagascar: a description of two hotspot districts - Sitraka Rakotosamimanana; Daouda Kassie; François Taglioni; Josélyne Ramamonjisoa; Fanjasoa Rakotomanana; Minoarisoa Rajerison (BMC, 2021)
Abstract Background Human plague cases, mainly in the bubonic form, occur annually in endemic regions of the central highlands of Madagascar. The aim of this study was to compare the dynamics of the epidemiological features of the human plague in two districts of the central highlands region. Methods In Madagascar, all clinically suspected plague cases that meet clinical and epidemiological criteria specified in the World Health Organization (WHO) standard case definition are reported to the national surveillance system. Data on plague cases reported between 2006 and 2015 in the districts of Ambositra and Tsiroanomandidy were analysed. Statistical comparisons between the epidemiological characteristics of the two districts were conducted. Results A total of 840 cases of plague were reported over the studied period, including 563 (67%) probable and confirmed cases (P + C). Out of these P + C cases, nearly 86% (488/563) were cases of bubonic plague. Reported clinical forms of plague were significantly different between the districts from 2006 to 2015 (p = 0.001). Plague cases occurred annually in a period of 10 years in the Tsiroanomandidy district. During the same period, the Ambositra district was characterized by a one-year absence of cases. Conclusion The differences in the epidemiological situation with respect to the plague from 2006 to 2015 in the two central highlands districts may suggest that several factors other than biogeographical factors determine the representation of the plague and its dynamics in this region. Considering the epidemiological situations according to the specific contexts of the districts could improve the results in the fight against the plague in Madagascar.